Stabilization of delayed neutral semi-Markovian jumping stochastic systems driven by fractional Brownian motions: H∞ control approach - Xu, Xiao; Wang, Li; Kao, Yonggui; Du, Zhenbin (Journal of the Franklin Institute, 2023)
This paper is devoted to the stochastic H∞ control of uncertain delayed neutral semi-Markovian jumping systems subject to fractional Brownian motions (fBms) with H∈(12,1). Firstly, a novel Lyapunov–Krasovskii functional (LKF) with exponential terms is constructed. Secondly, by means of leveraging the derivation rule, Wirtinger inequality, Schur complement and linear matrix inequalities (LMIs), stability analysis and controller gains are retrieved. Finally, through a simulation example, the control scheme is validated to be reasonable and effective.